Integrating Islamic Values and Local Wisdom: Ruwah Desa as a Multicultural Spiritual Response to Disasters - Novitasari, Nur Laila; Sirojuddin, Ahmad Sholihin; Muhammad, Jarir Kholil (Al-Insyiroh: Jurnal Studi Keislaman, 2025)
This study aims to examine the Ruwah Desa tradition in Kedungpapar Village as a form of local wisdom that strengthens the community’s social, cultural, psychological, mystical, and religious life. The research employed a descriptive qualitative approach with observation, interviews, and documentation, analyzed thematically to explore the meaning and function of the tradition. Findings reveal that Ruwah Desa plays a crucial role in preserving cultural identity, reinforcing social solidarity, and fostering a sense of security and togetherness. Moreover, it embodies mystical dimensions believed to maintain balance between humans and unseen forces, as well as religious dimensions expressed in gratitude to God and respect for ancestors. Thus, Ruwah Desa in Kedungpapar is not merely an annual ritual but also a medium for cultural preservation, value transmission, and the strengthening of social harmony that remains relevant amid contemporary life dynamics